2020
DOI: 10.1177/1745506520952045
|View full text |Cite
|
Sign up to set email alerts
|

Saudi women’s physical activity habits during pregnancy

Abstract: Background: Despite many benefits of physical exercise to women during pregnancy, the majority of Saudi women do not engage in an adequate amount of activity because of common barriers such as fatigue, lack of motivation, and childcare. The purpose of this study was to estimate the proportion of Saudi women who get adequate exercise during pregnancy as well as to evaluate their knowledge of, attitude toward, and barriers to physical exercise during pregnancy. Methods: This study had a cross-sectional design. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 24 publications
2
7
1
Order By: Relevance
“…Additionally, the same study showed that women who rated their own health status as excellent had adequate exercise with an odds ratio of 2.5 with reference to those who rated their own health status as being fair or poor. [ 15 ] In Riyadh city, approximately 42% of pregnant women reported high levels of awareness and practice physical activity, which were comparable to our study and concordant with the previous study. Furthermore, authors reported significant association of the level of awareness and practice with higher parity, educational level, and socioeconomic rank.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Additionally, the same study showed that women who rated their own health status as excellent had adequate exercise with an odds ratio of 2.5 with reference to those who rated their own health status as being fair or poor. [ 15 ] In Riyadh city, approximately 42% of pregnant women reported high levels of awareness and practice physical activity, which were comparable to our study and concordant with the previous study. Furthermore, authors reported significant association of the level of awareness and practice with higher parity, educational level, and socioeconomic rank.…”
Section: Discussionsupporting
confidence: 92%
“…[8–11] However, due to persisting misconceptions and lack of knowledge or support, majority pregnant women tend to have sedentary lifestyle especially in the third trimester. [ 2 12 13 14 15 16 ]…”
Section: Introductionmentioning
confidence: 99%
“…Our study echoes similar findings affecting the attitude of women to engage in prenatal physical activity. 22,26,28,32 These modifiable barriers expressed by the women in our study highlight the need to tailor context-specific interventions to address their concerns. Attitude regulates one's predisposition toward behaviour, 33 and in this case, toward prenatal physical activity; therefore, information on women's positive attitudes and knowledge on prenatal physical activity suggest interventions should target educational messages on the benefits and importance of engaging in prenatal physical activity to improve maternal health outcomes.…”
Section: A H E a D O F P R I N Tmentioning
confidence: 87%
“…Although there were no significant differences as a result of the analysis, self-care agency was higher in women who had a spouse with a high level of education, did not smoke, went to regular pregnancy controls, did not receive any training about pregnancy, exercised regularly, and had a chronic disease. In a study, it was recommended that women should be encouraged for physical activity for a healthy pregnancy (20). It was interesting that self-care agency was high in those who did not receive any training about pregnancy and that health care professionals had low self-care agency compared to other occupational groups.…”
Section: Discussionmentioning
confidence: 99%